THE INTERNSHIP STUDENTS’ PERFORMANCE FROM THE PERSPECTIVE OF INDUSTRY: CASE OF ISLAMIC BANKING STUDENTS - Ferri Nasrul; Mohamad Azwan Md Isa; Zaibedah Zaharum; Nur’Asyiqin Ramdhan; Mardziyan Mohamad Malom (Journal of Islamic, Social, Economics and Development, 2020)
Internship program is increasingly essential and set as one of the graduation requirements by the higher education institutions. The internship is significant in assessing students’ capability in applying theories and knowledge. In addition, the internship is aimed at exposing and equipping the students with important skills before they get involved in actual working environment. Therefore, this study aims to examine the effectiveness of internship program and to gauge the interns’ performance and their preparedness to face the real career world from the perspective of employers or industry. The analysis is based on the descriptive statistics, reliability and correlation tests besides the qualitative information provided by the industries. Using a sample of 387 students from the Bachelor of Business Administration (BBA) in Islamic Banking and covering the internship period from semesters March 2017 to March 2019, we found that overall interns’ performance evaluated by the industries is categorized as ‘Good’ because the mean score for all 18 measured areas is above 4.0 out of 5.0, respectively. The industries highlighted that the students possess many good attributes such as positive attitude, discipline and responsibility towards tasks. However, we noted that 89.5 percent of the Islamic Banking students had not undertaken the internship at the banking industry. Moreover, approximately 60 percent of the interns had been positioned in departments that are not relevant to banking or business. The industries suggested the interns to improve their communication skills and self-confidence and prepare themselves with various knowledge to be employable and to stay relevant in the job market.